Exploring the uptake of genetically modified white maize by smallholder farmers: the case of Hlabisa, South Africa - Mahlase, Mankurwana H (Department of Environmental and Geographical Science, 2017)
The use of genetically modified (GM) crops to resolve food security and poverty issues has been met with controversy and scepticism. The rationale for this research was to highlight the nuanced reasons as to why smallholder farmers are motivated to use agricultural biotechnology. The aim of this study was to explore the uptake of GM maize by South African smallholder farmers in order to contribute towards understanding the implications of agricultural biotechnology in smallholder agriculture. Using the case studies of Hlabisa in KwaZulu-Natal, the objectives were; (i) to investigate the perceived benefits and problems associated with the uptake of GM maize. (ii) to identify which institutional, political, social, and environmental factors influence the choices and decisions made by smallholder farmers to grow GM maize and (iii) to assess how GM maize has affected the well-being of farmers, including social cohesion in the farming communities. The reason Hlabisa was selected for the case study is that it represents one of the few areas in South Africa where GM crops (white GM maize in particular) has been cultivated on a long term basis by smallholder farmers. The necessary information was obtained through the means of a survey in which a number of farmers in the Hlabisa area participated in this regard the participants were; 40 farmers who used white GM maize that possessed the herbicide tolerant and insect resistant traits; seven farmers who used white insect resistant maize and 11 non-GM maize farmers. In addition, five key informant interviews and three focus group discussions were used to collect data. The history of agriculture in the area reveals that modern maize varieties were introduced when agricultural extension officers started operating in the area, beginning with maize seed hybrids in the 1970s. Maize hybrids were framed as better varieties compared to traditional maize in terms of performance. Later, in the 2000s, the seed company Monsanto, and the local department of agriculture introduced various GM maize varieties through farmers' days. This marked the addition of another institution providing so-called expert knowledge about maize farming in Hlabisa. It was argued that relationships between the local department of agriculture, farmers' associations and seed companies were instrumental in encouraging the uptake of GM maize seeds. It is also posited that the GM maize farmers in this study received pseudo-extension and advisory services. These had the agenda of promoting GM maize varieties over traditional varieties, relaying inappropriate agricultural knowledge in the process. There was also a lack of transparency in communicating the potential health and environmental risks associated with GM maize farming. Farmers were unaware that they were legally not allowed to save and exchange the patented GM maize seeds and had to plant refugia to prevent insect resistance. The uptake of GM maize has not significantly affected the seed saving and exchange practices of farmers. Fifty-two percent (24) of the 47 respondents no longer exchanged or saved any of their maize seeds in the study. A chi-squared test for independence indicated that the GM maize farmers were less likely to save and exchange seeds. The non-GM maize farmers were deterred from planting GM crops by the expensive input costs. The issue of affordability of the GM technology also extended to GM farmers, most of whom used social grants to purchase their GM maize seeds. Forty-nine percent of these farmers were in debt due to their uptake of the GM maize. Despite this debt, 74% of respondents claimed that they had perceived an improvement in their quality of life after using white GM maize, as they harvested enough maize to last them to the next planting season and were able to sell surplus maize. However, they only made marginal profits to cover household expenses. There are several conclusions that can be drawn from this study. First, there is a noticeable shift from farmers relying on their own knowledge and experience to using that of seed companies and agricultural extension officers. Second, Seed companies are beginning to fill the gaps left by public extension and advisory institutions and farmers are vulnerable to making uninformed decisions as they are not given relevant information. It is recommended that farmers are given agency through the provision of transparent information. This should be the responsibility of the government and not seed companies with vested interests. The government should try to move away from the idea that farmers need to scale up production through using modern varieties. A better approach would be the strengthening of appropriate support and extension services for South African smallholder farmers who use various maize systems. Lastly there is a need to raise awareness about the social, economic and environmental implications to farmers who elect to use GM seeds.